The ultimate Mac entertainment center. - Stern, Zack.
Wishing you could cut your ties to the cable company forever? You can. You can broaden your video entertainment choices and spend less each month with an Apple tech-based home-media setup. We show you exactly how.
Keywords: Apple TV (Digital media receiver); Internet; Home computer networks; Entertainment computing